Employing extant stable carbon isotope data in Gulf of Mexico sedimentary organic matter for oil spill studies. (July 2016) - Rosenheim, Brad E.; Pendergraft, Matthew A.; Flowers, George C.; Carney, Robert; Sericano, José L.; Amer, Reda M.; Chanton, Jeff; Dincer, Zeynep; Wade, Terry L.
Abstract: We have compiled and mapped available carbon isotope data from sedimentary organic material sampled from the Gulf of Mexico prior to 2010. These data provide a baseline to which any changes in the Gulf of Mexico after the 2010 Deepwater Horizon oil spill can be compared. The mean (±1 σ ) δ 13 C values, relative to PDB, are −21.4±1.9‰ (entire Gulf of Mexico), −21.7±1.2‰ (shelf sediments), −20.4±1.6‰ (deepwater sediments), and −25.2±4.1‰ (seep-affected sediments). We compare pre-spill mean δ 13 C values to carbon isotope measurements of sedimentary organic material from coretop samples collected after the 2010 Deepwater Horizon oil spill. The differences between the mean compiled δ 13 C values and the post-spill δ 13 C values are corroborated by qualitative relationships with the concentration of polycyclic aromatic hydrocarbons (PAHs), a proxy for oil contamination, in the sediment. The relationships between δ 13 C of the sedimentary organic material and PAH concentrations allow estimation of background levels of PAHs on the shelf and in the deep Gulf of Mexico. Higher background levels of PAH on the shelf likely relate to Mississippi River outflow and its deposition of petrogenic PAH in riverine sediments.